Environmental Literacy and Its Impact on Sustainable Pedagogical Behaviors of Basic Education Teachers, Lima-Peru - VÁSQUEZ TOMÁS, MELBA RITA (2022)
“Environmental literacy is the ability to perceive environmental conditions, become aware, make decisions and carry out actions to reestablish balance in the living environment and, through sustainable behaviors, protect the environment, guaranteeing the quality of life of people. The purpose of the study was to determine the incidence of environmental literacy in the sustainable pedagogical behaviors of basic education teachers. The research was carried out under a quantitative approach with the participation of 650 teachers from private and state schools in Metropolitan Lima, who, through the survey technique and instruments such as the questionnaire and the behavior scale, were able to determine their predominant level of literacy, as well as the type of sustainable pedagogical behavior. The results indicate that 385 teachers (59.23%) have a medium level of literacy, while 503 teachers (77.08%) have very adequate sustainable behaviors, concluding that environmental literacy has a 21% impact on the sustainable pedagogical behaviors of teachers. “